2022
DOI: 10.3389/fbinf.2022.885983
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Functions for Protein-Ligand Binding Affinity Prediction Using Structure-based Deep Learning: A Review

Abstract: The rapid and accurate in silico prediction of protein-ligand binding free energies or binding affinities has the potential to transform drug discovery. In recent years, there has been a rapid growth of interest in deep learning methods for the prediction of protein-ligand binding affinities based on the structural information of protein-ligand complexes. These structure-based scoring functions often obtain better results than classical scoring functions when applied within their applicability domain. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 383 publications
0
48
0
Order By: Relevance
“…Scoring of minimum-energy poses indicated that 3 had the best scoring pose with binding affinity measured using the Vina approach 32 of −8.433 kcal/mol, which was better than the parent compound (1, −7.5 kcal/mol) (Table 2). This was further supported by the improved Vinardo scoring function, 33,34 which held true even after local minimization of the top poses.…”
Section: Molecular Docking Of Ivacaftor Derivativesmentioning
confidence: 75%
“…Scoring of minimum-energy poses indicated that 3 had the best scoring pose with binding affinity measured using the Vina approach 32 of −8.433 kcal/mol, which was better than the parent compound (1, −7.5 kcal/mol) (Table 2). This was further supported by the improved Vinardo scoring function, 33,34 which held true even after local minimization of the top poses.…”
Section: Molecular Docking Of Ivacaftor Derivativesmentioning
confidence: 75%
“…26 However, docking does not allow estimation of affinity. 48,49 The observation that cGMP inhibits ATPase activity of purified NKA only at supraphysiological concentrations makes it unlikely that the effects of cGMP on Na + reabsorption result from direct ATPase inhibition. However, dopamine and other hormones reduce Na + flux in RPTCs indirectly by NKA internalization.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Applications of more recently developed techniques such as gradient boosting, deep neural networks, and transformers to early-phase drug discovery have been very successful, including applications to molecular docking. [33][34][35][36] Here, we combined the CP framework with several state-of-the-art classification algorithms to develop a workflow for accelerated structure-based virtual screening. We demonstrate that our most efficient workflow identifies the topscoring compounds in ultralarge compound libraries and reduces the number of molecules to be explicitly docked by three orders of magnitude.…”
Section: Recent Breakthroughs In Artificial Intelligence Have Revived...mentioning
confidence: 99%